Biomedical health monitoring system design and analysis - Nur Athilah Abdul Rahman; Asral Bahari Jambek (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
e-Health remote monitoring systems have bloomed rapidly with a myriad of applications. This paper discusses a design of a remote monitoring device for biomedical field. Four biomedical sensors which are electrocardiography (ECG), airflow, galvanic skin response and temperature with two boards which are the e-Health Shield Board V2.0 and Arduino Uno Board are used. The results show satisfactory output for each experiment using two test subjects. The device able to achieve high accuracy where percentage of temperature difference is less than 1% compared to the commercial devices with an average power consumption of each working sensor on board is ≤9W.